2020
DOI: 10.1038/s41467-020-14398-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the prefusion-locking broadly neutralizing antibody RVC20 bound to the rabies virus glycoprotein

Abstract: Rabies virus (RABV) causes fatal encephalitis in more than 59,000 people yearly. Upon the bite of an infected animal, the development of clinical disease can be prevented with postexposure prophylaxis (PEP), which includes the administration of Rabies immunoglobulin (RIG). However, the high cost and limited availability of serum-derived RIG severely hamper its wide use in resource-limited countries. A safe low-cost alternative is provided by using broadly neutralizing monoclonal antibodies (bnAbs). Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 29 publications
7
42
1
Order By: Relevance
“…In the quest for a novel therapeutic possibility, we have previously reported the selection of two human monoclonal antibodies (mAbs), RVC20 and RVC58, that were able to bind to two distinct antigenic sites on the RABV glycoprotein protein (sites I and III), to potently neutralize RABV isolates of all lineages, and of all phylogroup I non‐RABV isolates, and that presented a protective role when used as early PEP in hamsters as well (De Benedictis et al , 2016; Hellert et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the quest for a novel therapeutic possibility, we have previously reported the selection of two human monoclonal antibodies (mAbs), RVC20 and RVC58, that were able to bind to two distinct antigenic sites on the RABV glycoprotein protein (sites I and III), to potently neutralize RABV isolates of all lineages, and of all phylogroup I non‐RABV isolates, and that presented a protective role when used as early PEP in hamsters as well (De Benedictis et al , 2016; Hellert et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed the crystal structures of RABV G and its interaction with neutralizing antibodies (Hellert et al, 2020;Yang et al, 2020). Residues from G333-G350 of ectodomain from three strains (CVS-11, Flury, and SAD-B19) are observed to bond to antibody 523-11 (Yang et al, 2020).…”
Section: Figure 5 | (A)mentioning
confidence: 76%
“…Such a mechanism would explain the disparity in neutralizing activity between mAbs 93k and SG2, with the latter not binding to either the N-terminus or β30, which our previous study and this study demonstrate are essential regions for gB fusion function. There have been several studies demonstrating that mAbs can prevent viral fusion proteins from undergoing conformational changes [50-52]. A single study to date provides some evidence that a similar phenomenon is plausible for herpesvirus gB [53].…”
Section: Discussionmentioning
confidence: 99%